2019
DOI: 10.1002/ddr.21495
|View full text |Cite
|
Sign up to set email alerts
|

The protective effect of kaempferol on heart via the regulation of Nrf2, NF‐κβ, and PI3K/Akt/GSK‐3β signaling pathways in isoproterenol‐induced heart failure in diabetic rats

Abstract: This study was designed to delineate the effect of kaempferol (KF) on heart failure (HF) in diabetic rats. Streptozotocin‐induced male diabetic rats received KF orally at 10 and 20 mg/kg for 42 consecutive days. In last 2 days of the experimental period, isoproterenol was subcutaneously injected at 85 mg/kg to induce HF. The hearts were processed for hemodynamic, biochemical, molecular, and histological investigations. Systolic blood pressure, diastolic blood pressure, and mean arterial blood pressure were ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
48
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(66 citation statements)
references
References 66 publications
5
48
1
Order By: Relevance
“…and prevents the formation of hydroxyl radicals (OH -) by chelating several ions like ferrous and cuprous (Van Acker et al 1996;Mira et al 2002). Furthermore, kaempferol increases the expression of several antioxidant enzymes and GSH by upregulating their master regulator including nuclear Nrf-2, and the heme oxygenase-1 gene (Maridonneau-Parini 1986;Ozgova et al 2003;Doronicheva et al 2007;Hong et al 2009;Calder on-Montaño et al 2011;Zhang et al 2019). Therefore, it is possible that kaempferol improved MnSOD and GSH in the livers of the control and APAP-treated rats by upregulation/activation of the Nrf-2/HO-1 axis.…”
Section: Discussionmentioning
confidence: 99%
“…and prevents the formation of hydroxyl radicals (OH -) by chelating several ions like ferrous and cuprous (Van Acker et al 1996;Mira et al 2002). Furthermore, kaempferol increases the expression of several antioxidant enzymes and GSH by upregulating their master regulator including nuclear Nrf-2, and the heme oxygenase-1 gene (Maridonneau-Parini 1986;Ozgova et al 2003;Doronicheva et al 2007;Hong et al 2009;Calder on-Montaño et al 2011;Zhang et al 2019). Therefore, it is possible that kaempferol improved MnSOD and GSH in the livers of the control and APAP-treated rats by upregulation/activation of the Nrf-2/HO-1 axis.…”
Section: Discussionmentioning
confidence: 99%
“…Study shows that calycosin and formononetin inhibit the activation of the renin-angiotensin-aldosterone system to improve the symptoms of HF [29]. Kaempferol plays a cardioprotective role by inhibiting Nrf2, NF-κB, and Akt/GSK-3β signaling pathways to reduce apoptosis [30]. Hederagenin reduces the cascade of inflammatory responses by inhibiting IKKβ/NF-κB signaling pathway to improve coronary hemorheology and regulate endothelial dysplasia [31].…”
Section: Discussionmentioning
confidence: 99%
“…Of these, kaempferol (Kae) is well known for its pharmacological ability to reduce oxidative stress and inflammation in various organs and tissues ( Kampkotter et al., 2007 ; Park et al., 2009 ; Ren et al., 2019 ). Recent studies have demonstrated the protective effects of Kae on the heart by regulating nuclear factor erythroid-2 related factor (Nrf2) and nuclear factor kappa B (NF-κB) ( Suchal et al., 2016 ; Chen et al., 2018 ; Zhang et al., 2019 ). Of these factors, Nrf2, a master transcription factor, is transferred to the nucleus after activation, where it binds to the upstream cis-regulated antioxidant response element (ARE) sequence located in the promoter regions of genes responsible for cell protection ( David et al., 2017 ).…”
Section: Introductionmentioning
confidence: 99%